VD_FINDINFO Arrêt / 2016 / 470 vom 13. Juni 2016 - VD Tribunal cantonal (2016)
NOUVELLE DEMANDE, MOYEN DE PREUVE, TRANSMISSION D'UN ACTE PROCÉDURAL, COMPÉTENCE | 57a al. 1 LAI, 69 al. 1 let. a LAI, 30 LPGA, 56 LPGA, 58 LPGA, 87 al. 2 RAI, 87 al. 3 RAI